O livro didático pré e pós BNCC: uma análise das tarefas à luz do nível de funcionamento do conhecimento e letramento estatístico - Evangelista, Fernanda Miranda (2025)
This dissertation presents the results of a research study aimed at analyzing the changes that occurred in collections approved in the PNLD editions of 2018 and 2021, motivated by the implementation of the Brazilian Common Core Curriculum (BNCC) and the new program guidelines with a focus on the thematic unit, Statistics. The investigation focused on the tasks proposed by the textbooks, characterizing them according to the levels of knowledge functioning (Technical, Mobilizable, Available) and statistical literacy. Two collections were analyzed: Matemática: Contexto e Aplicações (Dante, 2016) and Matemática em Contextos (Dante & Viana, 2020). The analysis was based on the theories of Robert (1998) and Gal (2002). The results revealed that 90.6% of the statistics tasks in the 2018 collection and 87.1% in the 2021 collection are limited to the application and consolidation of formulas and concepts in a procedural manner, without inviting students to question or evaluate the data presented, thus restricting the full development of statistical literacy. In the 2021 version, the addition of the Situations section was observed at the beginning of the chapters, featuring problem situations contextualized in everyday life. Regarding the number of tasks, it was found that the amount in the current version 12 more than doubled compared to the previous one. As for the classifications, the predominance of technical levels and literacy skills was identified in both versions. However, in the current version there was an increase in tasks classified as mobilizable level, which involve situations requiring knowledge of more than one content area, in addition to critical questions, which gained space in the current version. No task classified as critical questions was identified in the PNLD 2018 collection. Finally, tasks categorized as available levels remained stable. These results indicate specific advances toward more complex learning experiences, but also highlight the need to expand the space for activities that encourage interpretation, argumentation, and decision-making based on data, thus strengthening students’ statistical literacy.